Uzależnienie od pornografii jako forma uzależnienia behawioralnego - Cicha, Daria Aleksandra (2019)
Today's addiction to pornography occurs with increasing frequency. Pornography as a phenomenon created in the nineteenth century grows in strength and takes on different faces. Pornography is a phenomenon that is socially downplayed as a result of society getting accustomed to this form of sexuality, which is another danger because it can lead to addiction. Addiction to pornography is a form of so-called behavioral addiction. Behavioral addiction in psychological terminology means a form of disorder related to the repetition of certain activities in the addictive stage. A special feature of behavioral addiction is the lack of an addictive addictive stimulus in the form of a psychoactive substance. Behavioral addiction is based on performing activities with limited ability to make free decisions, and these activities provoke the body to produce specific substances, e.g. increased dopamine ejection. The elements of behavioral addiction are: preoccupation, mood modification, tolerance, withdrawal symptoms, conflict (intrapersonal, interpersonal), relapses, and consequences: conflicts between addicted person and family and loved ones, internal conflict of an addicted person, reevaluation of pornography over work as a source of livelihood and passions , sexual dysfunction with appearing complexes in terms of appearance or distorted perception of men and women in terms of their subjectivity and social roles. The catalog of consequences referred to above does not constitute a closed catalog
Keywords: pornografia; uzależnienie behawioralne; uzależnienie od pornografii